2013
DOI: 10.1039/c2ob26673c
|View full text |Cite
|
Sign up to set email alerts
|

Use of benzynes for the synthesis of heterocycles

Abstract: About two decades after Kobayashi's discovery in 1983 of a very mild way of generating highly reactive aryne intermediates, the synthetic community embraced o-(trimethylsilyl)aryl triflates as convenient and versatile aryne precursors for the synthesis of carbocycles and heterocycles, as well as natural products and pharmaceutically promising drug candidates. This review provides a comprehensive overview of the construction of heterocycles using Kobayashi's silylaryl triflate aryne precursors. It is organized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(118 citation statements)
references
References 101 publications
1
117
0
Order By: Relevance
“…Arynes are highly reactive intermediates useful for preparing diverse aromatic compounds [1][2][3][4][5][6][7][8]. Novel transformations of arynes have been achieved and applied to the synthesis of a wide range of complex aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Arynes are highly reactive intermediates useful for preparing diverse aromatic compounds [1][2][3][4][5][6][7][8]. Novel transformations of arynes have been achieved and applied to the synthesis of a wide range of complex aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently the strained cyclic ynamide 11 can be generated in situ by addition of caesium fluoride, a procedure best known from the preparation of arynes. [55][56][57][58][59][60][61][62][63] To our delight, the strain-promoted sydnone ynamide cycloaddition tolerated a wide range of substitutions on the C4 position of the sydnone, as shown in Scheme 4. Reaction optimization revealed that slight excess of the sydnone provided best results, since when activated ynamides were used in excess, complex reaction mixtures were obtained, presumably due to side reactions.…”
Section: -32mentioning
confidence: 99%
“…The diastereomers of 11 were separated by PTLC (hexane/toluene/CH2Cl2/Et2O = 82/10/6/2 X2), affording less polar 11 and more polar 11 as white solids. ,7,9,14,16,18:7,16:9,. According to the procedure described for the synthesis of cycloadduct 6a, cycloadduct 11 (more polar) (35.1 mg, 0.0482 mmol), isobenzofuran 9c (14.7 mg, 0.0544 mmol) and n-BuLi (1.60 M in n-hexane, 0.040 mL, 0.064 mmol) gave, after purification by silica-gel flash column chromatography (hexane/CH2Cl2/Et2O = 96/3/1→88/9/3), 5,7,9,14,16,18-hexaphenyl-5,18:7,16:9,14-triepoxyheptacene (13) as a mixture of diastereomers (29.0 mg, 68.0%, ds.…”
Section: General Informationmentioning
confidence: 99%
“…We previously reported dual annulations of dibromoisobenzofuran 1, a formal equivalent of didehydroisobenzofuran A, via [2+4] cycloadditions of aryne [1][2][3][4][5][6][7][8][9] and isobenzofuran [10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Scheme 1). Selective bromine-lithium exchange from the starting two dibromides 2 and 3 enables the tandem generation of arynes and dual cycloadditions with two different arynophiles (step 1 and step 2).…”
Section: Introductionmentioning
confidence: 99%